Study on Rainfall Effects on Corn (Zea mays L.) Productivity in Ngawi Regency - Hariyono, Didik; Ramadhani, Palupi Dwi; Zaini, Akbar Hidayatullah; Saitama, Akbar (International Journal of Environment, Agriculture and Biotechnology, 2024)
The demand for corn in Indonesia is currently quite high, in line with the growing population and the increasing need for corn to meet the feed industry. Corn productivity has increased due to the expansion of land area and has not yet reached its yield potential due to climate change. Climate is a determining factor for the success of crop cultivation, thus it is necessary to study the relationship between climate elements and their effects on corn productivity in Ngawi Regency. The study was conducted from September to November 2022 using the survey method. The location was determined using purposive sampling technique directly determined by the researchers based on the corn production centers in Ngawi Regency. The chosen research locations were Pitu, Bringin, and Kendal Subdistricts. The climate classification in Pitu Subdistrict, Bringin Subdistrict, and Kendal Subdistrict has climate types D, C, and C, respectively. Correlation test results show that in Pitu Subdistrict, there is no significant correlation between rainfall intensity, rainy days, wet months, and dry months with corn productivity. Rainy days show a significant positive correlation with corn productivity in Bringin Subdistrict, while in Kendal Subdistrict, rainfall intensity and rainy days show a significant negative correlation with corn productivity.